Badania typu "tajemniczy klient" a jakość obsługi klienta w banku - Rudnik, Marcin (Quality Research of Customer Service in a Bank, 2008)
The problem of quality service is one of common topics of discussion among banks. Mystery shopping is a tool used by banks to measure quality of retail service. These banks send mystery shoppers to act as shoppers to interact with the business as a normal customer and report on the experience. The tool can also be used for the management of the quality and performances of goods and services. The aim of the foregoing article is to present mystery shopping method on the example of selected bank in Poland.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 33, s. 165-178